PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU PADA SMAN MODEL LOMBOK TIMUR - Salihin Salihin; Hermanto Hermanto; Lalu M. Furkan (Distribusi - Journal of Management and Business, 2020)
The challenge of education in delivering high quality and highly competitive human resources is increasingly, so teachers are required to always improve their performance in the world of education. Nanmu to achieve the high teacher's performance is required in-depth studies for the factors that affect the teacher's performance in carrying out its duties. Therefore, the purpose of this research is to know the influence of Transformational leadership style and the commitment of the Organization to the performance of teachers in SMA Model in East Lombok district. Analysis carried out using a qualitative, ununionized approach, conducted using structural equation Modeling (SEM) based on partial least square (PLS), using 97 respondents. The results of this study show that the Transformational leadership style has a positive influence on the teacher's performance at SMA Model in East Lombok. Organizational commitment has a positive but insignificant relationship to the performance of teachers in SMA Model East Lombok District.